Adaptive Dose Escalation using Serial Four-dimensional Positron Emission Tomography/Computed Tomography Scans during Radiotherapy for Locally Advanced Non-small Cell Lung Cancer. Issue 12 (December 2016) - Yap, M.L.; Sun, A.; Higgins, J.; Clarke, K.; Marshall, A.; Becker, N.; Le, L.W.; Vines, D.C.; Bezjak, A.; Bissonnette, J.-P.
Abstract: Aims: Computed tomography (CT)-based radiotherapy dose escalation for locally advanced non-small cell lung cancer (LA-NSCLC) has had limited success. In this planning study, we investigated the potential for adaptive dose escalation using respiratory-gated 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography scans (4DPET/4DCT) acquired before and during a course of chemoradiotherapy (CRT). Materials and methods: We prospectively enrolled patients with LA-NSCLC receiving curative intent CRT. Radiotherapy was delivered using intensity-modulated radiotherapy (IMRT) using the week 0 4DCT scan. Three alternative, dose-escalated IMRT plans were developed offline based on the week 0, 2 and 4 4DPET/4DCT scans. The FDG-avid primary (PET-T) and nodal disease (PET-N) volumes defined by the 50% of maximum standard uptake value threshold were dose escalated to as high as possible while respecting organ at risk constraints. Results: Thirty-two patients were recruited, 27 completing all scans. Twenty-five patients (93%) were boosted successfully above the clinical plan doses at week 0, 23 (85%) at week 2 and 20 (74%) at week 4. The median dose received by 95% of the planning target volume (D95) at week 0, 2 and 4 to PET-T were 74.4 Gy, 75.3 Gy and 74.1 Gy and to PET-N were 74.3 Gy, 71.0 Gy and 69.5 Gy. Conclusions: Using 18F-FDG-4DPET/4DCT, it is feasible to dose escalate both primary and nodal disease in most patients. Choosing week 0 images to plan a course with an integrated boost to PET-avid disease allows for more patients to be successfully dose escalated with the highest boost dose.